PENGARUH PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) PADA BAHASAN PECAHAN UNTUK MENUMBUHKAN KEPERCAYAAN DIRI DAN MENINGKATKAN HASIL BELAJAR SISWA SMP - Yusuf, Asep; Mubarok, Ruslan; Zanthy, Luvy Sylviana (IKIP Siliwangi, 2020)
This study aims to increase confidence in learning mathematics and improve learning outcomes by applying NHT type cooperative learning models to the subject of fractions. This type of research is one group pretest-posttest design experimental research subjects with class VII-B, amounting to 25 people. To retrieve the data, an instrument was used in the form of a test sheet about fractions as many as 5 question descriptions and a questionnaire about confidence in learning mathematics as many as 25 statements. The results of research before and after treatment are: (1) self-confidence can affect the improvement of student learning outcomes. (2) before getting treatment the student grades were still relatively low with an average grade of 59. (3) after getting treated with NHT type cooperative learning, student learning outcomes improved with an average value of 75.2.